Solutions for Tropical Vertical Motion under Convective Quasi-Equilibrium Constraints - Dang, Dong-Pha; Yu, Jia-Yuh (Journal of the atmospheric sciences, 2024)
Solutions for tropical convection (vertical motion), including both the first (deep) and the second baroclinic (shallow) modes, subject to convective quasi-equilibrium (CQE) constraints are formulated. Under CQE assumption, tropical convection ω ( p , x , y ) can be decomposed into a product of height-dependent variable Ω i ( p ) and space-dependent variable ∇· v i ( x , y ) with the former constrained by conservation of moist static energy (MSE) or dry static energy (DSE) perturbations, depending on whether the atmospheric column is dominated by ascending or descending motions. We then evaluate the roles of deep and shallow modes of convection in transporting moisture and static energy against observations using the European Centre for Medium-Range Weather Forecasts reanalysis data. The moisture transport by deep mode produces a spatial pattern similar to observations, except for an obvious underestimate of the magnitude over the eastern Pacific convergence zone (EPCZ) and cold tongue areas, where the contribution of shallow mode may account for up to 25% of the total moisture transport. In contrast, the MSE transport by deep mode exhibits a very poor performance, especially over the EPCZ where the observational MSE transport is negative, but a positive value is predicted by deep mode. Including the contribution of shallow mode immediately remedies this deficiency, due to a better representation of the bottom-heavy structure of ascending motions over the EPCZ. These improvements apply to almost the entire tropics, although the correlation tends to decrease away from the convergence zones. Since simple atmospheric models often assume a single heating (forcing) profile to represent the effect of cumulus convection, the present study highlights the importance and feasibility of including both deep and shallow modes in a simple atmospheric model, while at the same time maintaining the simple model framework, to more accurately represent the moisture and MSE transports by convection in the tropics.